Application of a flexible coordination polymer Mn-dhbq in the separation of NF3 and CF4
Patent Information
- Application Number
- CN202611152298.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
考虑到两者物化性质的极度接近,刚性MOF受限于固定的孔道尺寸,同样难以胜任
本发明将Mn-dhbq的温度调控"门控开启"行为与动态填充柱分离、产物纯度、吹扫再生、循环稳定性、放大合成及造粒成型等关键工艺指标进行了系统性关联。在常温条件下,Mn-dhbq选择性允许NF3进入孔道,同时有效抑制CF4的共吸附,从而在吸附阶段直接获得高纯度CF4,脱附阶段则以温和吹扫方式回收高纯度NF3。该材料可在室温水相中实现百克级合成,并可与羟乙基纤维素(HEC)黏结剂复合造粒,造粒后仍能保持优异的动态分离性能,为吸附剂从实验室发现到填充柱工程应用提供了可能。
Smart Images

Figure CN122998890A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of MOF material gas separation technology, and specifically relates to the application of a flexible coordination polymer Mn-dhbq in the separation of NF3 and CF4. Background Technology
[0002] The rapid development of the semiconductor industry has led to an ever-increasing demand for high-purity electronic specialty gases. Nitrogen trifluoride (NF3), due to its superior etching performance and selectivity compared to most perfluorocarbons, has become an indispensable plasma etchant and reaction chamber cleaning gas in integrated circuit manufacturing. However, in the industrial process of preparing NF3 by electrolyzing NH4F in a fluorine-rich medium using carbon electrodes as anodes, carbon tetrafluoride (CF4) inevitably occurs as a co-product. Furthermore, since fluorine-containing gases in semiconductor processes are often only partially consumed, the final exhaust gas contains both NF3 and CF4, necessitating proper disposal or resource recovery.
[0003] Currently, industrial NF3 / CF4 separation relies heavily on cryogenic distillation or azeotropic distillation. However, their boiling points are extremely close (NF3 144.11 K, CF4 145.11 K), differing by only about 1 K, resulting in extremely high energy consumption, large equipment investment, and complex operation for thermal separation processes. Adsorption separation, as a potential low-energy alternative, cannot be judged solely on equilibrium adsorption capacity or ideal selectivity. A truly engineering-approved adsorbent must simultaneously meet several stringent requirements under packed column conditions: high dynamic product purity, considerable working capacity, mild regeneration conditions, excellent cycle stability, scalability for synthesis, and the ability to be molded into particles with sufficient mechanical strength for column packing.
[0004] The biggest obstacle to achieving the above goals lies in the high molecular similarity between NF3 and CF4. Their kinetic diameters differ by only about 1 Å (NF3 3.62 Å, CF4 4.66 Å), and their polarizabilities are also very close (NF3 36.2 × 10⁻⁶). -25 cm 3 CF438.4×10 -25 cm 3Traditional adsorbents such as zeolites and activated carbon, due to the lack of finely tunable pore structures, struggle to effectively distinguish such similar pairs of molecules. While metal-organic frameworks (MOFs), with their highly customizable pore environments, have demonstrated superior performance in olefin separation, volatile organic compound removal, and greenhouse gas capture, existing research has largely focused on capturing target components from mixtures of NF3 / CF4 and N2, a task significantly less challenging than the direct separation of NF3 and CF4. Given the extreme similarity in their physicochemical properties, rigid MOFs, limited by fixed pore sizes, are equally inadequate. In contrast, flexible frameworks have attracted considerable attention due to their ability to undergo reversible structural transformations triggered by pressure, temperature, or guest adsorption—their unique "gated opening" behavior dynamically couples molecular recognition with operating conditions, offering new possibilities for the extreme separation of NF3 / CF4. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides an application of the flexible coordination polymer Mn-dhbq in the separation of NF3 and CF4.
[0006] Furthermore, the flexible coordination polymer Mn-dhbq is formed by the coordination of Mn(II) ions with 2,5-dihydroxy-1,4-benzoquinone H2dhbq ligands to form a one-dimensional chain structure, with the chains stacked together by O–H···O hydrogen bonds to form a three-dimensional network. After activation and removal of coordination water, the long-range order of the one-dimensional chains is reduced, and the framework becomes flexible. Under the action of adsorbate molecules, the framework can undergo a reversible structural transformation, realizing the switching of pore closure and opening.
[0007] Furthermore, at operating temperatures of 298 K and below, NF3 can overcome the gating barrier and enter the Mn-dhbq channel, while CF4 is blocked outside the channel due to insufficient adsorption driving force, thereby achieving selective separation of NF3 / CF4.
[0008] Furthermore, the adsorbed NF3 is desorbed and regenerated by purging with inert gas at room temperature, and the cycle stability is not less than 5 times.
[0009] Furthermore, the preparation method of Mn-dhbq includes the following steps: dissolving 2,5-dihydroxy-1,4-benzoquinone H2dhbq and Mn(CH3COO)2·4H2O in deionized water, and magnetically stirring at room temperature for 24-36 h. After the reaction is completed, centrifuge, wash with deionized water, and vacuum dry.
[0010] Furthermore, the molar ratio of H2dhbq and Mn(CH3COO)2·4H2O is 1:1, and the amount of deionized water added is 10 mL of deionized water for every 1.5 mmol.
[0011] The present invention also provides an adsorbent particle for separating NF3 and CF4, the adsorbent particle comprising Mn-dhbq powder and binder hydroxyethyl cellulose (HEC), wherein the mass ratio of Mn-dhbq powder to binder hydroxyethyl cellulose is 19:1.
[0012] Beneficial technical effects of the present invention: This invention systematically correlates the temperature-controlled "gating" behavior of Mn-dhbq with key process indicators such as dynamic packed column separation, product purity, purging regeneration, cycle stability, scale-up synthesis, and granulation. At room temperature, Mn-dhbq selectively allows NF3 to enter the pores while effectively inhibiting the co-adsorption of CF4, thus directly obtaining high-purity CF4 during the adsorption stage and recovering high-purity NF3 through gentle purging during the desorption stage. This material can be synthesized in 100-gram quantities in an aqueous phase at room temperature and can be granulated with hydroxyethyl cellulose (HEC) binder, maintaining excellent dynamic separation performance even after granulation. This provides a possibility for adsorbents to move from laboratory discovery to engineering applications in packed columns. Attached Figure Description
[0013] Figure 1 PXRD patterns of the original Mn-dhbq and the experimental samples.
[0014] Figure 2 Thermogravimetric analysis (TGA) curves of Mn-dhbq synthesized in small batches and at scale.
[0015] Figure 3 Coordination mode of the one-dimensional chain structure of Mn-dhbq (A); Perspective view of the synthetic state of Mn-dhbq along the c-axis (B); Hydrogen bond interaction between two adjacent one-dimensional chains (C).
[0016] Figure 4 A schematic diagram of the mechanism of Mn-dhbq before and after complete activation and during the adsorption process.
[0017] Figure 5 Scanning electron microscope (SEM) images of small-batch synthesized Mn-dhbq: (a) in the synthesized state; (b) after activation.
[0018] Figure 6 (A) N2 adsorption-desorption isotherm of activated Mn-dhbq at 77 K; (B) Adsorption isotherms of Mn-dhbq for NF3 / CF4 at different temperatures; (C) IAST separation selectivity of Mn-dhbq for NF3 / CF4 (50 / 50) mixture at 298 K; (D) Equivalent heat of adsorption of NF3 by Mn-dhbq.
[0019] Figure 7(A) Available pore space along the c-axis in the Mn-dhbq structure; and pore space along the b-axis (B). Adsorption and binding sites of NF3 in the one-dimensional Mn-dhbq framework determined by DFT simulation (C).
[0020] Figure 8 (A) Under conditions of 298 K and 100 kPa, NF3 / CF4 (50 / 50) mixture (5 mL•min) -1 The breakthrough adsorption and desorption process of the Mn-dhbq packed column (He purging, 5 mL•min) -1 (A) Five consecutive breakthrough cycles of Mn-dhbq for NF3 / CF4 (50 / 50) mixture; (B) Breakthrough curve of Mn-dhbq for NF3 / CF4 (1 / 9) mixture at 298 K.
[0021] Figure 9 Scanning electron microscope (SEM) images of Mn-dhbq samples after the penetration experiment.
[0022] Figure 10 (A) The entire process of Mn-dhbq preparation, drying and activation to granulation; (B) 77K N2 adsorption isotherms of Mn-dhbq samples after small-batch, scale-up synthesis and granulation; (C) Comparison of NF3 / CF4 (50 / 50) breakthrough curves of raw Mn-dhbq powder and 5 wt% HEC granulated sample.
[0023] Figure 11 Magnified scanning electron microscope (SEM) images of synthesized Mn-dhbq: (a) in the synthesized state; (b) after activation.
[0024] Figure 12 Particle size distribution of Mn-dhbq particles (5% binder).
[0025] Figure 13 Crushing strength of Mn-dhbq granulated sample (5 wt% HEC). Detailed Implementation
[0026] Example 1: Small-batch synthesis 2,5-Dihydroxy-1,4-benzoquinone (1.5 mmol, 0.21 g) and Mn(CH3COO)2·4H2O (1.5 mmol, 0.37 g) were dissolved in 10 mL of deionized water and magnetically stirred at room temperature for 24 h. After the reaction was complete, the mixture was centrifuged, washed three times with deionized water, and the resulting sample was dried under vacuum at 60 °C for 12 h. The product yield was approximately 78%.
[0027] The material prepared in Example 1 was characterized, and the results are as follows: The phase purity of the material prepared in Example 1 was confirmed by powder X-ray diffraction (PXRD). Figure 1 Thermogravimetric analysis (TGA) shows that this material has excellent thermal stability. Figure 2 The weight loss below 150℃ is attributed to the removal of Mn(II) coordinated water, after which the structural stability of Mn-dhbq can be maintained at approximately 450℃.
[0028] In the crystal structure, each Mn(II) ion coordinates with four oxygen atoms from two H2dhbq ligands, forming a one-dimensional linear chain. Figure 3 A), while two water molecules occupy axial coordination sites at the center of Mn(II). Adjacent one-dimensional chains are connected by extensive OH···O hydrogen bond interactions between coordinated water molecules and ligand oxygen atoms, forming a three-dimensional hydrogen-bonded supramolecular network ( Figure 3 B,C). Mn-dhbq exhibits swelling flexibility. After complete activation, the removal of coordination water weakens the long-range order of the crystal, while simultaneously enabling the material to adsorb specific guest molecules, accompanied by a partial recovery of order. Figure 4 Scanning electron microscopy (SEM) images showed that the synthetic Mn-dhbq was in the form of blocky particles, while the activated particles had a more linear morphology, consistent with the weakening of interchain interactions and the decrease in order. Figure 5 ).
[0029] The permanent porosity of Mn-dhbq was first evaluated using the N2 adsorption isotherm at 77 K. The equilibrium N2 adsorption capacity of this sample was 125 cm⁻¹. 3 ·g -1 The corresponding pore volume is approximately 0.19 cm³. 3 ·g -1 ( Figure 6 A). Its BET specific surface area is calculated to be 467.5 m². 2 ·g -1 .
[0030] The adsorption performance of Mn-dhbq for NF3 / CF4 was further investigated. Single-component adsorption isotherms at 298 K showed that NF3 could be effectively adsorbed by Mn-dhbq, with an adsorption capacity as high as 1.24 mmol·g at 1 bar. -1 CF4, on the other hand, has difficulty diffusing into the pores; at 1 bar, it is only adsorbed on the surface, with an adsorption capacity of only 0.13 mmol·g. -1 ( Figure 6(B) The NF3 / CF4 adsorption ratio reaches 9.3. Therefore, Mn-dhbq can achieve efficient NF3 / CF4 sieving at 298 K. Similar adsorption behavior was observed at 323 K. When the adsorption temperature drops to 273 K, the adsorption capacity of Mn-dhbq for NF3 increases, but CF4 can also diffuse into the pores at this point. The stepwise adsorption behavior of CF4 at 273 K indicates that Mn-dhbq exhibits a significant "gating" effect on CF4, with a sharp increase in CF4 adsorption at 273 K and 50 kPa. CF4 adsorption is dominated by a temperature-dependent skeletal transformation process. At 273 K, the adsorption driving force is sufficient to overcome the free energy barrier of gating, while at 298 K and above, within the achievable pressure range, the driving force is insufficient to trigger pore opening, gating is suppressed, and CF4 adsorption becomes negligible. Therefore, to suppress CF4 co-adsorption as much as possible, operation should be carried out at relatively high temperatures to avoid the gating effect of Mn-dhbq on CF4.
[0031] Furthermore, the separation selectivity was calculated based on the Ideal Adsorption Solution Theory (IAST). The separation selectivity of Mn-dhbq for an equimolar (50 / 50) NF3 / CF4 mixture at 298 K and 323 K reached 10.6 and 15.8, respectively. Figure 6 C). The selectivity at 298 K surpasses that of several previously reported materials, including HKUST-1 (1.35), Mn3(HCOO)6 (2.71), SBMOF-1 (1.93), and ATC-Cu (2.16). Meanwhile, the isotropic heat of adsorption (Q) of NF3 calculated based on the virial equation is also significantly higher. st The value is 21.8 kJ·mol⁻¹ -1 ( Figure 6 D), lower than ATC-Cu (39.8 kJ·mol). -1 ), SBMOF-1 (28.8 kJ·mol) -1 ) and Ni-MOF (28.8 kJ·mol -1 This relatively low heat of adsorption can be attributed to the unique flexible structural features of Mn-dhbq: some of the energy released during NF3 adsorption is used to drive the phase transition of the framework, rather than being entirely converted into heat of adsorption.
[0032] To further elucidate the adsorption mechanism of NF3 on Mn-dhbq, density functional theory (DFT) simulations were used to study the host-guest interaction. In the presence of coordinated water, Mn-dhbq can be considered a dense, closed-pore structure; however, after the removal of coordinated water, the nanochannels and cavities extending along the one-dimensional chains open, allowing NF3 molecules to diffuse into the pores. Figure 7A, B). Dehydration reduces the long-range order of Mn-dhbq, making its actual pore structure more complex. Therefore, to simplify calculations while closely approximating reality, a one-dimensional segment of Mn-dhbq is extracted as the host model for adsorption simulation. Given the strong electronegativity of fluorine atoms in NF3, Lewis acid sites in Mn-dhbq can act as adsorption sites interacting with NF3. First, dehydration exposes abundant open metal sites in Mn-dhbq, which can form Mn···F interactions with NF3. Furthermore, the benzene ring and hydrogen atoms in the ligand can also act as adsorption sites, forming π···F and H···F interactions with NF3, respectively. DFT calculation results ( Figure 7 C) indicates that the main adsorption site of NF3 in Mn-dhbq is located above the benzene ring of the ligand. The three fluorine atoms of NF3 participate in F···Mn, F···H, and F···π interactions, respectively, with interaction distances of 3.68, 3.42, and 3.20 Å. The calculated binding energy of NF3@Mn-dhbq is 23.4 kJ·mol⁻¹. -1 It is higher than 19.2 kJ·mol⁻¹ of CF₄@Mn-dhbq. -1 .
[0033] Dynamic packed column penetration test At 298 K, when an equimolar NF3 / CF4 feed is introduced into a Mn-dhbq packed column, CF4-induced gating opening is effectively suppressed. For example... Figure 8 As shown in Figure A, CF4 rapidly exits the cylinder, while NF3 is retained for 6 min·g. -1 The fact that it only emerged later indicates that the co-adsorption of CF4 by Mn-dhbq was effectively suppressed. High-purity CF4 (≥99.5%) could be directly collected at this stage, with a dynamic CF4 yield of 0.37 mmol·g. -1 Subsequently, the mixture was purged with He at room temperature (5 mL / min). -1 During the desorption process, high-purity NF3 (≥99.5%) was recovered with a yield of 0.42 mmol·g. -1 After reactivation, the excellent separation performance of Mn-dhbq remained stable in at least five consecutive breakthrough cycles. Figure 8 B). Furthermore, the PXRD patterns and morphology of the recycled Mn-dhbq samples remained well-preserved compared to the original samples. Figure 1 and 9 Mn-dhbq also achieved effective separation of the NF3 / CF4 = 90 / 10 mixture. Figure 8(C) This composition is closer to the composition of actual NF3-rich process gas flow than the equimolar system. The above results demonstrate that Mn-dhbq not only possesses equilibrium selectivity but also exhibits comprehensive performance characteristics suitable for practical applications, including high dynamic product purity, recoverable working capacity, mild purge-regeneration conditions, and excellent cycle stability. Example 2: Scale-up Synthesis The synthesis was carried out on a 1000-fold scale-up scale in a 10L reactor. H₂dhbq (1.5 mol, 210 g) and Mn(CH₃COO)₂·4H₂O (1.5 mol, 370 g) were dissolved in 10L of deionized water and stirred at room temperature for 36 h. After the reaction was complete, the mixture was filtered, washed six times with deionized water, and the resulting sample was dried under vacuum at 60 °C for 12 h. The product yield was approximately 72%.
[0034] Example 3 Preparation of Mn-dhbq particles Coordination polymer particles were prepared using hydroxyethyl cellulose (HEC) as a binder. 19g of activated Mn-dhbq powder was uniformly mixed with 1g of HEC, and 10mL of deionized water was added in five portions, grinding and mixing thoroughly after each addition. The resulting wet paste was extruded into spherical particles with a diameter of approximately 2mm, which were then air-dried.
[0035] Scalable synthesis and particle shaping are key steps in translating adsorbent performance into packed column operation. Currently, many MOF materials are still limited to small-scale laboratory synthesis, relying on expensive precursors and toxic organic solvents. In contrast, Mn-dhbq uses relatively inexpensive precursors and can be synthesized in an aqueous phase at room temperature. After process optimization, Mn-dhbq achieved 100-gram-scale preparation with a space-time yield of 42 kg·m³. -3 ·d -1 ( Figure 10 A). Although the particle size of the scaled-up synthetic sample is smaller than that of the small batch sample ( Figure 11 However, their pore structures are basically the same. Figure 10 B), BET specific surface area is 417.2m². 2 ·g -1 .
[0036] The above-scaled synthetic powder was further granulated into spherical particles using 5wt% hydroxyethyl cellulose (HEC) as a binder. The resulting Mn-dhbq@5%HEC particles had a diameter of approximately 3-4 mm. Figure 12 The crushing strength of this particle is 24-29 N, indicating that its mechanical strength is sufficient to meet the requirements of packed column operation. Figure 13 The BET specific surface area of Mn-dhbq@5%HEC particles, as determined by N2 adsorption at 77K, was 326.2 m². 2 ·g -1 ( Figure 5B). Breakthrough experiments showed that the dynamic NF3 adsorption capacity of the granulated particles was retained at approximately 71% of that of the powder sample. Figure 10 C). The decrease in specific surface area and dynamic adsorption capacity may stem from the dilution effect of the binder, partial pore blockage, and / or intraparticle mass transfer resistance introduced during the granulation process. Nevertheless, Mn-dhbq successfully achieved a balance between room-temperature aqueous phase synthesis at the 100g scale, excellent mechanical strength in HEC granulation, and dynamic separation performance, providing a possibility for NF3 / CF4 recovery to move from material discovery to practical application in packed columns. In summary, Mn-dhbq achieved the adsorption and separation of NF3 / CF4 at room temperature through a temperature-controlled "gated opening" molecular sieving mechanism. At 298K and 1 bar, the adsorption capacity of Mn-dhbq for NF3 was 1.24 mmol g. -1 It hardly adsorbs CF4 (0.136 mmol g), but hardly adsorbs CF4 (0.136 mmol g g). -1 IAST calculations show that for equimolar NF3 / CF4 mixtures, the selectivity at 298 K and 323 K is 10.6 and 15.8, respectively. The enthalpy of NF3 adsorption is 21.8 kJ·mol⁻¹. -1 It exhibits moderate strength, consistent with the response behavior of the flexible framework, which is beneficial for regeneration under mild conditions. Dynamic packed column experiments show that high-purity CF4 (≥99.5%) can be obtained during the adsorption stage, and high-purity NF3 (≥99.5%) can be recovered during the room-temperature He purge desorption stage, with this performance remaining stable over five cycles. Mn-dhbq can also be synthesized at a hundred-gram scale in an aqueous phase at room temperature and can be granulated with HEC binder to obtain particles with excellent mechanical strength, retaining approximately 71% of its dynamic NF3 adsorption capacity.
Claims
1. Application of a flexible coordination polymer Mn-dhbq in the separation of NF3 and CF4.
2. The application of the flexible coordination polymer Mn-dhbq according to claim 1 in the separation of NF3 and CF4, characterized in that: The flexible coordination polymer Mn-dhbq is formed by the coordination of Mn(II) ions with 2,5-dihydroxy-1,4-benzoquinone H2dhbq ligands to form a one-dimensional chain structure. The chains are stacked together by O–H···O hydrogen bonds to form a three-dimensional network. After activation and removal of coordination water, the long-range order of the one-dimensional chains is reduced, and the framework becomes flexible. Under the action of adsorbate molecules, the framework can undergo a reversible structural transformation, realizing the switching of pore closure and opening.
3. The application of the flexible coordination polymer Mn-dhbq according to claim 1 in the separation of NF3 and CF4, characterized in that: At operating temperatures of 298 K and below, NF3 can overcome the gating barrier and enter the Mn-dhbq channel, while CF4 is blocked outside the channel due to insufficient adsorption driving force, thus achieving selective separation of NF3 / CF4.
4. The application of the flexible coordination polymer Mn-dhbq according to claim 1 in the separation of NF3 and CF4, characterized in that: The adsorbed NF3 is desorbed and regenerated by purging with inert gas at room temperature, and the cycle stability is not less than 5 times.
5. The application of the flexible coordination polymer Mn-dhbq according to claim 1 in the separation of NF3 and CF4, characterized in that: The preparation method of Mn-dhbq includes the following steps: 2,5-dihydroxy-1,4-benzoquinone H2dhbq and Mn(CH3COO)2·4H2O are dissolved in deionized water and magnetically stirred at room temperature for 24-36 h. After the reaction is completed, the mixture is centrifuged, washed with deionized water, and vacuum dried.
6. The application of the flexible coordination polymer Mn-dhbq according to claim 5 in the separation of NF3 and CF4, characterized in that: The molar ratio of H2dhbq and Mn(CH3COO)2·4H2O is 1:1, and the amount of deionized water added is 10 mL of deionized water for every 1.5 mmol.
7. An adsorbent particle for separating NF3 and CF4, characterized in that: The adsorbent particles comprise Mn-dhbq powder as described in any one of claims 1-6 and hydroxyethyl cellulose (HEC) binder, wherein the mass ratio of Mn-dhbq powder to hydroxyethyl cellulose binder is 19:1.
